Crimes in the area of material goods in the revised Book VI of the 1983 Code of Canon Law - Domaszk, Arkadiusz (Prawo Kanoniczne, 2022)
Material goods serve above all to achieve ecclesiastical goals. Everyone who legally administers such goods should take care of the property affairs and undertake all necessary or needed administrative actions - like a good father of a family. Persons who serve as stewards of the Church's property and who hold certain ecclesiastical offices are bound by canon law and are subject to a duty of accountability. If irregularities, abuses and sometimes even canonical crimes occur in the administration of temporal goods, then the norms of criminal law must be applied. The paper will discuss those situations, which should be called crimes within the canon law and which concern material goods. Some of them have been present in the Code of Canon Law since its promulgation in 1983. The revision of Book VI of the Code made in 2021 confirmed some of the already existing solutions of the criminal law. It should be noted that the changes within Book VI of the Code have broadened the range of criminal acts that concern the administration of temporal goods. The order of the considerations undertaken partly refers to the arrangement of the code system in Book V of the Code. Crimes in relation to acquisition of goods, their administration and alienation are discussed accordingly. Thus, such acts as: simony; abuse of the offerings of the faithful and mass intentions; bribery; profanation; restriction of freedom in administration; misappropriation of goods and illegal alienation; disobedience; falsification of documents; abuse of power, office or task; violation of certain prohibitions binding on the clergy and religious.